Phosphorus-containing polymethacrylate viscosity index improver as well as preparation method and application thereof
By using phosphorus-containing polymethacrylate viscosity index improver in lubricating oil, the problem of insufficient friction reduction and wear resistance of lubricating oil in the prior art has been solved, and the multi-performance improvement of lubricating oil has been achieved.
Patent Information
- Application Number
- CN202411816498.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polymethacrylate (PMA) is a lubricant additive, and it is difficult to improve the friction-reduction and wear resistance of lubricant.
The phosphorus-containing polymethacrylate viscosity index improver was prepared by dissolving dodecane and 2-methyl-2-hydroxyethyl phosphate in 2-methyltetrahydrofuran, adding azobisisobutyronitrile and dodecanethiol.
Significantly improve the viscosity index, low-temperature performance, and high-temperature viscosity maintenance performance of lubricant oil, and significantly improve the friction-reduction and wear resistance of lubricant oil.
Smart Images

Figure CN119708330A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lubrication, and in particular relates to a phosphorus-containing polymethacrylate viscosity index improver, a preparation method and application thereof. Background Art
[0002] Viscosity index improver is one of the main categories of lubricant additives. It is an oil-soluble high molecular polymer that is mainly used to increase the viscosity index of lubricants and improve the low-temperature performance and high-temperature viscosity retention performance of lubricants. Currently, viscosity index improvers mainly include hydrogenated styrene diene copolymer (HSD), polymethacrylate (PMA), ethylene propylene copolymer (OCP), polyisobutylene (PIB) and other types. Among them, polymethacrylate has excellent low-temperature performance and high-temperature viscosity retention performance, and is used in a variety of lubricant products, especially in situations where a high viscosity index is required.
[0003] However, the polymethacrylate (PMA) currently available on the market has a relatively single function, which is mainly used to increase the viscosity index of lubricating oil, but it is difficult to improve the friction and wear resistance of lubricating oil. Therefore, providing a multifunctional viscosity index improver has good prospects and significance. Summary of the invention
[0004] The invention provides a viscosity index improver, which is a phosphorus-containing polymethacrylate viscosity index improver.
[0005] The preparation method of the above viscosity index improver comprises the following steps:
[0006] Dodecyl methacrylate and 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate are dissolved in 2-methyltetrahydrofuran; azobisisobutyronitrile and dodecanethiol are added, and the solution is purified with nitrogen; then a polymerization reaction is carried out, and air is injected into the reaction system to cool and terminate the reaction; the reaction product is precipitated in methanol to achieve the purpose of purification, and finally the obtained product is dried to obtain a viscosity index improver.
[0007] In the above preparation method, each component is selected from the following parts:
[0008] 10-30 parts of dodecyl methacrylate, 1-10 parts of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, 50-70 parts of 2-methyltetrahydrofuran, 0.1-0.3 parts of azobisisobutyronitrile, and 0.05-0.15 parts of dodecanethiol;
[0009] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0010] In a specific embodiment, each ingredient is selected from the following servings:
[0011] 21.31 parts of dodecyl methacrylate, 3.82 parts of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, 66.67 parts of 2-methyltetrahydrofuran, 0.201 parts of azobisisobutyronitrile, and 0.1005 parts of dodecanethiol;
[0012] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0013] In a specific embodiment, each ingredient is selected from the following servings:
[0014] 21.31 parts of dodecyl methacrylate, 2.73 parts of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, 63.78 parts of 2-methyltetrahydrofuran, 0.1923 parts of azobisisobutyronitrile, and 0.0961 parts of dodecanethiol;
[0015] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0016] In a specific embodiment, each ingredient is selected from the following servings:
[0017] 21.31 parts of dodecyl methacrylate, 2.12 parts of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, 62.16 parts of 2-methyltetrahydrofuran, 0.1874 parts of azobisisobutyronitrile, and 0.09372 parts of dodecanethiol;
[0018] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0019] In the above preparation method, the molar ratio of lauryl methacrylate to 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate is selected from 1:1 to 10:1; preferably 5:1, 7:1 and 9:1.
[0020] In the above preparation method, the polymerization reaction conditions are selected from: reacting at 65-85°C for 3-5h; preferably: reacting at 75°C for 4h.
[0021] The present invention provides the use of the viscosity index improver in improving the viscosity index, low temperature performance, high temperature viscosity retention performance and / or friction reduction and wear resistance of lubricating oil.
[0022] The present invention provides a high-performance lubricating oil, which is composed of the above-mentioned viscosity index improver and base oil; the mass ratio of the viscosity index improver to the base oil is 5:95.
[0023] The beneficial effects of the present invention are:
[0024] The present invention utilizes dodecyl methacrylate and 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate to synthesize a phosphorus-containing polymethacrylate viscosity index improver. The improver can significantly improve the viscosity index of lubricating oil, improve the low-temperature performance and high-temperature viscosity retention performance of the lubricating oil, and also has a good improvement effect on the friction reduction and wear resistance of the lubricating oil, thereby showing good application prospects and use value in the field of lubrication. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the infrared spectrum of the viscosity index improver;
[0026] Figure 2 This is the NMR phosphorus spectrum of the viscosity index improver (2P51);
[0027] Figure 3 This is the NMR phosphorus spectrum of the viscosity index improver (2P71);
[0028] Figure 4 This is the NMR phosphorus spectrum of the viscosity index improver (2P91);
[0029] Figure 5 is the friction coefficient curve of each implementation case;
[0030] Figure 6 is the wear volume of each implementation case;
[0031] Figure 7 The three-dimensional wear profile of comparative example 1;
[0032] Figure 8 The three-dimensional wear profile of comparative example 2;
[0033] Fig. 9 The three-dimensional wear profile of Example 1;
[0034] Fig.10 The wear three-dimensional profile morphology diagram of Example 2;
[0035] Fig.11 The wear three-dimensional profile morphology diagram of Example 3;
[0036] Fig.12 This is the XPS test result of the friction test block in Example 1. DETAILED DESCRIPTION
[0037] In the present invention, the base oil 150N was purchased from Formosa Petrochemical Corporation; the dodecyl methacrylate was purchased from Aladdin Reagent (Shanghai) Co., Ltd.; the viscosity index improver BASF-6300V was purchased from BASF; and the 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate was purchased from Maclean.
[0038] The present invention provides a viscosity index improver, which is prepared by the following method:
[0039] Lauryl methacrylate (LMA) and 2-methyl-2-acrylic acid-2-hydroxyethyl phosphate (PM-2) are dissolved in 2-methyltetrahydrofuran (2-MeTHF); azobisisobutyronitrile (AIBN) and dodecanethiol are added, and the solution is purified with nitrogen; then a polymerization reaction is carried out, and air is injected into the reaction system to cool and terminate the reaction; the reaction product is precipitated in methanol to achieve the purpose of purification, and finally the obtained copolymer is dried to obtain a viscosity index improver.
[0040] The reaction formula is as follows:
[0041]
[0042] In the above-mentioned method for preparing the viscosity index improver, the molar ratio of dodecyl methacrylate to 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate is selected from 1:1 to 10:1; preferably 5:1, 7:1 and 9:1. The viscosity index improvers prepared at these three ratios are referred to as 2P51, 2P71 and 2P91, respectively.
[0043] Other materials used in the present invention, if not otherwise stated, can be obtained through commercial channels. Other terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The present invention is further described in detail below in conjunction with specific examples and with reference to data. The following examples are only for illustrating the present invention, and are not intended to limit the scope of the present invention in any way.
[0044] Preparation Example 1
[0045] The viscosity index improver (2P51) was prepared as follows:
[0046] Dodecyl methacrylate (21.31 g, 83.8 mmol) and 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate (3.82 g, 16.75 mmol) were dissolved in 66.67 mL 2-methyltetrahydrofuran. Azobisisobutyronitrile (0.2010 g, 0.8%) and dodecyl mercaptan (0.1005 g, 0.4%) were added, and the solution was purged with nitrogen for 30 min. The reaction system was then placed in a 75°C oil bath for polymerization. After 4 h of reaction, the reaction was stopped by cooling and opening the flask to contact air. The copolymer was placed in an excess (10 times) of methanol for precipitation to achieve purification purposes, and the copolymer was purified three times in total. The copolymer was then dried overnight at room temperature to obtain a viscosity index improver, referred to as 2P51.
[0047] Preparation Example 2
[0048] The viscosity index improver (2P71) was prepared as follows:
[0049] Dodecyl methacrylate (21.31 g, 83.8 mmol) and 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate (2.73 g, 11.97 mmol) were dissolved in 63.78 mL 2-methyltetrahydrofuran. Azobisisobutyronitrile (0.1923 g, 0.8%) and dodecyl mercaptan (0.0961 g, 0.4%) were added, and the solution was purged with nitrogen for 30 min. The reaction system was then placed in a 75°C oil bath for polymerization. After 4 h of reaction, the reaction was stopped by cooling and opening the flask to contact air. The copolymer was placed in an excess (10 times) of methanol for precipitation to achieve the purpose of purification. The copolymer was purified three times in total, and then the copolymer was dried overnight at room temperature to obtain a viscosity index improver, referred to as 2P71.
[0050] Preparation Example 3
[0051] The viscosity index improver (2P91) was prepared as follows:
[0052] Dodecyl methacrylate (21.31 g, 83.8 mmol) and 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate (2.12 g, 9.31 mmol) were dissolved in 62.16 mL 2-methyltetrahydrofuran. Azobisisobutyronitrile (0.1874 g, 0.8%) and dodecyl mercaptan (0.09372 g, 0.4%) were added, and the solution was purged with nitrogen for 30 min. The reaction system was then placed in a 75°C oil bath for polymerization. After 4 h of reaction, the reaction was stopped by cooling and opening the flask to contact air. The copolymer was placed in an excess (10 times) of methanol for precipitation to achieve purification purposes, and the copolymer was purified three times in total. The copolymer was then dried overnight at room temperature to obtain a viscosity index improver, referred to as 2P91.
[0053] The infrared spectrum of the above viscosity index improver is as follows: Figure 1 As shown: There is basically no C=C characteristic peak in the infrared spectra of the three polymers, indicating that polymerization reaction has occurred.
[0054] The NMR phosphorus spectra of the above viscosity index improvers are as follows: Figure 2 to Figure 4 As shown: the corresponding characteristic peak P(=OR)3 appears in the NMR phosphorus spectrum, indicating that phosphorus-containing polymethacrylate has been successfully synthesized.
[0055] Example 1
[0056] To prepare lubricating oil, follow these steps:
[0057] 2.5 g (5 wt%) of viscosity index improver 2P51 and 47.5 g (95 wt%) of base oil 150N were added into a container in sequence. Mechanical stirring was started and the temperature was raised to 50°C and stirred for 10 min. The temperature was raised to 75°C and stirred for 30 min. The lubricating oil was then cooled to room temperature to obtain the lubricating oil.
[0058] Example 2
[0059] To prepare lubricating oil, follow these steps:
[0060] 2.5 g (5 wt%) of viscosity index improver 2P71 and 47.5 g (95 wt%) of base oil 150N were added into a container in sequence. Mechanical stirring was started and the temperature was raised to 50°C and stirred for 10 min. The temperature was raised to 75°C and stirred for 30 min. The mixture was then cooled to room temperature to obtain lubricating oil.
[0061] Example 3
[0062] To prepare lubricating oil, follow these steps:
[0063] 2.5 g (5 wt%) of viscosity index improver 2P91 and 47.5 g (95 wt%) of base oil 150N were added into a container in sequence. Mechanical stirring was started and the temperature was raised to 50°C and stirred for 10 min. The temperature was raised to 75°C and stirred for 30 min. The lubricating oil was then cooled to room temperature to obtain the lubricating oil.
[0064] Comparative Example 1
[0065] To prepare lubricating oil, follow these steps:
[0066] Base oil 150N 50.0g, add the above components into a container, start mechanical stirring, heat to 50°C, continue stirring for 10 minutes, heat to 75°C, continue stirring for 30 minutes, and then cool to room temperature to obtain lubricating oil.
[0067] Comparative Example 2
[0068] To prepare lubricating oil, follow these steps:
[0069] BASF-6300V 2.5g (5wt%) viscosity index improver, 150N base oil 47.5g (95wt%), add the above components into a container in sequence, start mechanical stirring, heat to 50°C, continue stirring for 10min, heat to 75°C, continue stirring for 30min, and then cool to room temperature to obtain lubricating oil.
[0070] 1. Comprehensive performance research test
[0071] 1. Viscosity index
[0072] The kinematic viscosity of lubricating oil is tested according to the NB / SH / T 0870-2020 standard, and the viscosity index of lubricating oil is tested according to the GB / T 1995-1998 standard, and the thickening ability of lubricating oil is evaluated.
[0073] The test results are shown in Table 1:
[0074] Table 1 Viscosity index of each implementation case
[0075]
[0076]
[0077] It can be seen from Table 1 that the viscosity index improver prepared by the present invention can effectively improve the viscosity index of lubricating oil, and 2P51 and 2P71 have stronger capabilities than the foreign product BASF-6300V.
[0078] 2. Tribological properties
[0079] The oil sample was ground for 30 minutes using the SRV-IV micro-vibration friction and wear tester produced by Optimol Grease Company of Germany at 50°C, frequency 25Hz, stroke 1mm, load 150N, and the average friction coefficient f was obtained. The steel ball used in the test was GCr15 bearing steel with a diameter of 10mm, and the block used for the lower sample had a diameter of 24mm and a height of 7.9±0.1mm. The wear scar of the lower sample steel block after SRV friction was characterized using MicroXAM 3D non-contact three-dimensional surface profiler.
[0080] The experimental results are shown in Table 2. Figure 5 , Figure 6 and Figure 7 to Figure 11 As shown:
[0081] Table 2 Tribological properties of various implementation cases
[0082] Group Average friction coefficient <![CDATA[Wear volume (×10 3 μm 3 )]]> Example 1 0.114 48 Example 2 0112 69 Example 3 0.111 52 Comparative Example 1 0.221 623 Comparative Example 2 0.175 258
[0083] As can be seen from Table 2, the friction coefficient and wear volume of the lubricating oils added with 2P51, 2P71, and 2P91 viscosity index improvers are significantly better than those of the lubricating oils added with BASF-6300V viscosity index improver, which indicates that the phosphorus-containing polymethacrylate viscosity index improver prepared in the present invention has a beneficial effect on the friction reduction and anti-wear performance of the lubricating oil; compared with the base oil without the viscosity index improver, the friction coefficient of the base oil added with the phosphorus-containing polymethacrylate viscosity index improver is significantly reduced, and the wear volume is reduced by one order of magnitude, indicating that the phosphorus-containing polymethacrylate viscosity index improver prepared in the present invention has a good friction reduction and anti-wear effect.
[0084] The XPS test analysis was performed on the lower test block of SRV friction and wear in Example 1. Fig.12 As shown, it can be seen from the test results that the main components of the friction film are Fe2O3 and FePO4, which shows that the phosphorus-containing viscosity index improver prepared in the present invention can form a FePO4 friction film with Fe, and the presence of the FePO4 friction film can effectively reduce the friction coefficient of the friction pair surface and reduce the occurrence of wear.
[0085] In summary, the phosphorus-containing polymethacrylate viscosity index improver prepared by the present invention can significantly improve the viscosity index of lubricating oil and improve the low-temperature and high-temperature viscosity stability of lubricating oil. At the same time, P in the phosphorus-containing viscosity index improver reacts with Fe in the friction pair to generate FePO4, which can reduce the friction coefficient of the friction pair surface and improve its anti-wear ability. The phosphorus-containing polymethacrylate viscosity index improver prepared by the present invention has the good effect of improving the viscosity index of lubricating oil and reducing friction and anti-wear performance, and has broad application prospects.
[0086] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A viscosity index improver, characterized in that: The improver is a phosphorus-containing polymethacrylate viscosity index improver.
2. The method for preparing the viscosity index improver according to claim 1, characterized in that: The steps include: Dodecyl methacrylate and 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate are dissolved in 2-methyltetrahydrofuran; azobisisobutyronitrile and dodecanethiol are added, and the solution is purified with nitrogen; then a polymerization reaction is carried out, and air is injected into the reaction system to cool and terminate the reaction; the reaction product is precipitated in methanol to achieve the purpose of purification, and finally the obtained product is dried to obtain a viscosity index improver.
3. The preparation method according to claim 2, characterized in that: The ingredients are selected from the following quantities: 10 to 30 parts of dodecyl methacrylate, 1 to 10 parts of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, 50 to 70 parts of 2-methyltetrahydrofuran, 0.1 to 0.3 parts of azobisisobutyronitrile, and 0.05 to 0.15 parts of dodecanethiol.
4. The preparation method according to claim 3, characterized in that: The ingredients are selected from the following quantities: 21.31 parts of dodecyl methacrylate, 3.82 parts of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, 66.67 parts of 2-methyltetrahydrofuran, 0.201 parts of azobisisobutyronitrile, and 0.1005 parts of dodecanethiol.
5. The preparation method according to claim 3, characterized in that: The ingredients are selected from the following quantities: 21.31 parts of dodecyl methacrylate, 2.73 parts of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, 63.78 parts of 2-methyltetrahydrofuran, 0.1923 parts of azobisisobutyronitrile, and 0.0961 parts of dodecanethiol.
6. The preparation method according to claim 3, characterized in that: The ingredients are selected from the following quantities: 21.31 parts of dodecyl methacrylate, 2.12 parts of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, 62.16 parts of 2-methyltetrahydrofuran, 0.1874 parts of azobisisobutyronitrile, and 0.09372 parts of dodecanethiol.
7. The preparation method according to claim 2, characterized in that: The molar ratio of the lauryl methacrylate to the 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate is selected from 1:1 to 10:
1.
8. The preparation method according to claim 2, characterized in that: The polymerization reaction conditions are selected from: reacting at 65-85° C. for 3-5 hours.
9. Use of the viscosity index improver according to claim 1 or the viscosity index improver prepared by the method according to any one of claims 2 to 8 in improving the viscosity index, low temperature performance, high temperature viscosity retention performance and / or friction reduction and wear resistance of lubricating oil.
10. A high performance lubricating oil, characterized in that: The lubricating oil is composed of the viscosity index improver according to claim 1 or the viscosity index improver prepared by the method according to any one of claims 2 to 8 and a base oil; the mass ratio of the viscosity index improver to the base oil is 5:95.
Citation Information
Patent Citations
Lubricant composition with phosphorus-functionalized polymers
CN103443257A
Additive composition for lubricating oil and lubricating oil composition
CN116529276A
Copolymers useful as multifunctional additives in lubricants, and compositions containing these copolymers
EP0309317A1
Viscosity index-improver and lubricating oil composition
JP2009149874A
Cited By
Viscosity index improver with extreme pressure anti-wear property as well as preparation method and application of viscosity index improver
CN120518816A